Comparison of the Performance of Feed A and Feed B on Productivity and Cost Efficiency at Surodadi Farm, Sleman - Dahri Tanjung; Ananda Manurung; Warcito Warcito; Yeti Lis Purnamadewi (Postgraduate, University of Mataram, 2025)
This study aims to evaluate the productivity and feed efficiency of laying hens through a comparative analysis of two commercial feed types, Feed A and Feed B. A quantitative approach was employed, utilizing independent samples t-test and Revenue to Cost (R/C) ratio analysis. Sample size was determined using Slovin's formula based on uniform criteria of flock size, age, and cage dimensions, resulting in a minimum requirement of 385 hens. To improve accuracy, 2952 Lohmann Brown hens (35–54 weeks old) were used, distributed equally in two cages of 1476 hens each. Key performance indicators included Hen Day Production (HDP), egg mass (g/hen/week), Feed Conversion Ratio (FCR), and net income. The results showed that Feed B provided better performance across all metrics. HDP for Feed B reached 91.49%, higher than Feed A at 88.75%. Total egg mass produced per cage for Feed B was 1638 kg, exceeding Feed A at 1554 kg. Feed B also recorded a more favorable FCR (2.14 vs. 2.25), indicating more efficient feed utilization. Economically, although Feed B was slightly more expensive (IDR 6,352/kg) than Feed A (IDR 6,268/kg), it generated a higher net income of IDR 6,434,870 for the total flock (2952 hens) over the study period. The R/C ratio for Feed B was 1.21, compared to 1.15 for Feed A, indicating relatively greater profitability. These findings suggest that Feed B is a more efficient and economically advantageous option for commercial layer operations aiming to optimize productivity and returns.